Kehidupan hati : untuk sampai kepada Tuhan yang dikasihi - 'Imad al-Din al-Isnawi, Muhammad ibn al-Hasan, d. 1363; Salleh Karimi Mohd. Kari (Kuala Lumpur : Utusan Publications & Distributors, 2005)
35